Busana Unisex Berbasis Kain Tradisional Rangrang Bali - Dewi, Ni Putu Chyntia; Nyoman Dewi, Pebryani; Ida Ayu Gede, Artayani (Serat Rupa: Journal of Design, 2025)
This study aims to preserve the traditional Balinese Rangrang fabric through unisex fashion design combined with environmentally friendly fabrics. Through this approach, it is expected to support the preservation of Indonesian cultural heritage, create contemporary fashion so that it can compete in the global market, reduce fast fashion waste and meet the lifestyle of generation Z amidst the flow of globalization. This preservation is not only to preserve, but also as an effort to recognize Balinese Rangrang fabric in WBTBI (Indonesian Intangible Cultural Heritage), as we know that this fabric has not been recognized in WBTBI, even though this fabric has been passed down from generation to generation by the people of Nusa Penida. Using a descriptive qualitative approach, data was collected through a literature study on Balinese Rangrang fabric, the characteristics of unisex fashion and the characteristics of generation Z fashion. Interviews with weaving owners, weavers and desainers to obtain more in-depth information. The results of the study show that the design of deluxe ready-to-wear unisex fashion based on Balinese Rangrang fabric is an effective step to preserve Rangrang fabric and reduce fast fashion waste. This research contributes to the development of contemporary fashion that contains traditional values in modern fashion design that is relevant to the needs of generation Z.